Recursive Differential Evolution Algorithm for Inertia Parameter Identification of Space Manipulator. (31st May 2016) - Liu, Zhengxiong; Huang, Panfeng; Lu, Zhenyu
This paper proposes a recursive differential evolution (RDE) algorithm to identify the inertial parameters of an unknown target and simultaneously revise the friction parameters of space manipulator joints. The inertia parameters of a space manipulator, which govern the dynamic behaviours of the entire system to a significant extent, can change for many reasons during the process of on-orbit operations; consequently, it is essential to trace these changes within the control system to ensure the stability and accuracy of the entire system. RDE is inspired by a recursive least squares algorithm, using approximate gradient information to guide the mutation operation in the standard DE. A series of contrast simulations are employed to confirm the feasibility of the RDE algorithm. The simulation results show that the identification of the RDE algorithm is more precise than for a GA (genetic algorithm) and LS (least square) algorithm, and has an appropriate convergence rate. The RDE identification method is suitable for linear, nonlinear and combined systems, and can follow system dynamics exactly.